Influence of environmental growth temperature on tocopherol and sterol oil concentrations in olive fruit - Hamze, Leila (2021)
BACKGROUND: Tocopherols and sterols are minor components of virgin olive oils that contribute to oil quality. Based on observations at different geographical locations, it has been suggested that environmental temperature during fruit growth affects tocopherol and sterol oil concentrations in olive fruit. However, controlled experiments have not been conducted to directly assess their responses to temperature. In this study, a manipulative experiment using open top chambers (OTCs) was performed in the field to evaluate the responses of these oil components to a moderate air temperature increase during oil accumulation in young trees of two olive cultivars (Arbequina, Coratina). The two temperature levels in the OTCs were a control about 1°C above ambient temperature (T0) and a heated treatment (T+) with a target temperature of 4 °C above T0. RESULTS: Total tocopherol and sterol oil concentrations in olive fruit were generally higher in the T+ temperature treatment than in the control at the end of the oil accumulation period. The increase in total tocopherols in T+ appeared to be related to a decrease in fruit oil concentration with heating. Individual sterols showed both significant increases and decreases due to T+ and some differences in response occurred between the two cultivars. CONCLUSIONS: These findings provide evidence that growth temperature affects tocopherol and sterol oil concentrations in olive fruit at the end the oil accumulation period. Cultivars should be carefully chosen for new olive growing regions, and the results could be relevant for global warming scenarios in existing growing regions.